CITRA PEREMPUAN INDONESIA TAHUN 1965 DALAM NOVEL â€œADZRAâ€™ JAKARTAâ€ KARYA NAJIB KAELANI (KAJIAN NEW HISTORISME) - Muhayyan, Muhayyan; Ferawati, Ferawati (Universitas Ahmad Dahlan)
This article explains how Najib Kaelani erred in recognizing the impression of women in Indonesia in 1965 and his ideological tendencies in making narrative of them through his novel entitled Adzaâ€™ Jakarta. As a novel that is considered historical, it is inappropriate to tell the history with certain ideological tendencies. This research applies descriptive analysis method and uses New Historism theory to investigate the novel Adzraâ€™ Jakarta and then compare it with the history of Indonesia in 1965. The conclusion is that the impression of women in Indonesia in 1965 was more dynamic compared to women in Arab who are generally represented in Misogynist.